Implementasi Nilai-Nilai Akidah Akhlak Ibadah Oleh Guru PAI pada Siswa Kelas IX di SMP Muhammadiyah 1 Purwokerto - Sab’ati Mela Matsania; Makhful Makhful (UM Purwokerto Press, 2023)
Islamic values must be applied to students in order to instill a spiritual soul in a child's identity. The inculcation of Islamic values in schools can be applied through subjects, extracurriculars, or habits that must be carried out by students. The author chose Junior High School of Muhammadiyah 1 Purwokerto as a place of research because he saw deviant behavior carried out by students at some time including students who were truant, cheated, and said rudely in the school environment and dating. This study aims to provide an overview of the implementation of the values of faith, worship, and morals for the class IX students of Sekolah Menengah Pertama Muhammadiyah 1 Purwokerto. The type of research used is field research using a qualitative approach. The subjects of this study were grade IX students at Junior High School of Muhammadiyah 1 Purwokerto with data analysis techniques in the form of observation, interviews, and documentation, while the analysis provided a description in the form of a narrative about the implementation form under study. The author describes the indicators of the variables that are the center of research attention. The results of the study indicate that implementing religious practices organized by schools, especially at Junior High School of Muhammadiyah 1 Purwokerto, it provides an added value for schools, namely by implementing the values of aqidah morals of worship through learning in the classroom and learning outside the classroom such as providing material on faith, morality, worship and require students to perform the Duhur prayer in congregation, pray Duha in the congregation, get used to the 3S (Smile, Greet, Greeting), infaq on Fridays, attend extracurricular Tahsin and Tahfidz, read the Qur'an after prayer noon in the congregation.